MONEY POLITIC DALAM PERSPEKTIF SADDU AL-ZARIAH - Rahwan Rahwan (Universitas Halu Oleo, 2020)
Money politics is a political disease that is increasingly prevalent today. Money politics is a part of the bribery offense. In general, the criminal act of bribery is considered a violation in the world of politics, thus requiring money politics to also be considered a violation. In absolute terms, state laws and regulations explicitly prohibit this action, but this practice is rampant nonetheless. In Sharia law there is often discussion about risywah which is in the form of the millennial period which is reflected in the money political mechanism. However, Jurisprudence scholars in general still disagree over the law of certainty risywah. The editor of the Prophet's Hadith said that Rasulullah Saw. cursing the perpetrator and the recipient of the bribe. However, various interpretations of the scholars have resulted in an imbalance between positive legal regulations and Islamic law. By combining two legal decisions through the study of Ushūl Fikih with Saddu ad-Dzāriah's approach. This study will discuss legal decisions regarding risywah from a different perspective and prove that there is no imbalance between the two.